Comparative study of positive and negative ion flows extracted from downstream plasmas beyond magnetic and electrostatic electron filters - Dudin, S.; Rafalskyi, D.; Popelier, L.; Aanesland, A. (Физическая инженерия поверхности, 2012)
In the present paper we compare the positive and negative ion flows created using a recently developed
electrostatic grid-type filter with the flows formed using a magnetic filter. Langmuir probe measurements
show electron cooling with both filters, allowing effective formation of negative ions via electron
dissociative attachment in the region of low electron temperature. The energy distribution functions
of positive and negative ions extracted from the filtered plasmas are measured in both systems showing
an almost monoenergetic nature of the ions with the energy corresponding to the imposed extraction
potential. It is shown that in both cases strongly electronegative plasmas where the negative ion
density is much larger than the electron density can be formed downstream of the filter. Biasing an
internal electrode or the electrostatic filter grid allows control of the plasma potential. In the case of
the electrostatic filter the plasma could be biased negatively compared to ground and effective extraction
of negative ion was achieved. В данной работе проведено сравнение потоков положительных и отрицательных ионов, генерируемых с использованием недавно разработанного электростатического сеточного фильтра
с потоками, формируемыми с использованием магнитного фильтра. Измерения ленгмюровскими зондами показали эффективное “охлаждение” электронов при использовании обоих
фильтров, обеспечивающее условия для эффективного образования отрицательных ионов в
области с низкой электронной температурой в результате диссоциативного прилипания. Функции
распределения по энергии положительных и отрицательных ионов, извлекаемых из вторичной
плазмы, измеренные в обеих системах, показали моноэнергетичность генерируемых потоков
ионов с энергией, соответствующей приложенному извлекающему потенциалу. Показано, что
в обоих случаях возможно формирование сильно электроотрицательной плазмы на выходе
фильтра с плотностью отрицательных ионов значительно превышающей плотность электронов.
Смещение внутреннего электрода либо сетки фильтра позволило достичь управления потенциалом плазмы. В случае электростатического фильтра потенциал плазмы может принимать
отрицательные значения по отношению к заземленному электроду, благодаря чему было достигнуто эффективное извлечение отрицательных ионов. У даній роботі проведено порівняння потоків позитивних і негативних іонів, що генеруються з
використанням недавно розробленого електростатичного сіткового фільтру з потоками, що
формуються з використанням магнітного фільтру. Вимірювання ленгмюрівськими зондами показали ефективне “охолоджування” електронів при використанні обох фільтрів, що забезпечує
умови для ефективного утворення негативних іонів в області з низькою електронною температурою в результаті диссоціативного прилипання. Функції розподілу по енергії позитивних і
негативних іонів, витягуваних з вторинної плазми, виміряні в обох системах, показали моноенергетичність потоків іонів, що генеруються, з енергією, відповідною до прикладеного витягуючого потенціалу. Показано, що в обох випадках можливе формування сильно електронегативної плазми на виході фільтру з щільністю негативних іонів що значно перевищує
щільність електронів. Зсув потенціалу внутрішнього електроду або сітки фільтр дозволив досягти керування потенціалом плазми. У разі електростатичного фільтру потенціал плазми може
приймати негативні значення по відношенню до заземленого електроду, завдяки чому було
досягнуте ефективне витягання негативних іонів.